Multilayer blue polymer light-emitting devices with spin-coated interlayers - Duan, Lian; Chin, Byung Doo; Yang, Nam Choul; Kim, Mu-Hyun; Kim, Hye Dong; Lee, Seong Taek; Chung, Ho Kyoon (ELSEVIER SCIENCE SA, 2007)
Employment of multilayer heterostructures is a common approach to achieve efficiency and stable organic light emitting diodes (OLEDs). In this work, we report multilayer blue polymer light-emitting devices (PLEDs) by using spin-coated fluorene-triarylamine copolymers as interlayers between the conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT) and the emitting layer. A blue PLED with stepped hole injection profile yields an external quantum efficiency of 6.0% at a luminance of 9500 cd/m(2) at 5.5 V and an extrapolated lifetime of more than 18,000 h from 100 cd/m(2). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: INDIUM-TIN-OXIDE; DIODES; INTERFACE